Faktor-Faktor Yang Mempengaruhi Minat Generasi Millenial Menggunakan Qris BNI Mobile Sebagai Metode Pembayaran - Salam, Kartanegara; Hamdat, Amin; Mardianah, Mardianah; Alam, Nur; Ajelin, Ajelin (Movere Journal, 2024)
The purpose of this study was to determine the factors that influence the interest of millennials in using qris PT Bank Negara Indonesia (Persero) tbk as a payment method (case study of PT Bank Negara Indonesia (Persero), Tbk Mattoangin branch). The analysis method used is quantitative descriptive analysis using multiple regression analysis using SPSS 25 for windows. The results of the analysis show that security has a positive and insignificant effect on the desire to use QRIS. Ease has a positive and significant effect on the desire to use QRIS. And the benefits have a positive and significant effect on the desire to use QRIS